Progression on the Roles and Mechanisms of Tumor-Infiltrating T Lymphocytes in Patients With Hepatocellular Carcinoma - Zheng, Xiaoqin; Jin, Wenjie; Wang, Shanshan; Ding, Huiguo (Frontiers in Immunology, 2021)
Primary liver cancer (PLC) is one of the most common malignancies in China, where it ranks second in mortality and fifth in morbidity. Currently, liver transplantation, hepatic tumor resection, radiofrequency ablation, and molecular-targeted agents are the major treatments for hepatocellular carcinoma (HCC). Overall, HCC has a poor survival rate and a high recurrence rate. Tumor-infiltrating lymphocytes (TILs) have been discovered to play essential roles in the development, prognosis, and immunotherapy treatment of HCC. As the major component cells of TILs, T cells are also proved to show antitumor and protumor effects in HCC. Foxp3+, CD8+, CD3+, and CD4+ T lymphocytes are the broadly studied subgroups of TILs. This article reviews the roles and mechanisms of different tumor-infiltrating T lymphocyte subtypes in HCC.